Exploring the “Thigh-for-Marks” phenomenon among public universities in Zimbabwe - Mafa, Itai; Simango, Tapiwa (Springer, 2022)
While it remains uncontested that women and girls continue to face various kinds of sexual harassment at home, at work places and within societies, concerns over a trending phenomenon known as “thigh-for-marks” within university institutions have attracted close scrutiny from various interested stakeholders. This has prompted an exploration of the phenomenon in order to ascertain its implications on the educational as well as sexual and reproductive health rights of learners. Through qualitative lenses, the study found out that this form of sexual harassment is associated with intense psycho-emotional trauma, compromised educational output, loss of social capital and increased susceptibility to HIV/AIDS. Anchored on developmental social work principles, the paper advocates for robust sexual harassment policies within universities as well as clear reporting systems in order to safeguard the sexual and educational rights of students from outright infringement. The paper further argues for the adoption of a school social work model within institutions of higher learning in order to strengthen psycho-social support services in universities.